Parenting styles and psychopatology: the importance of grandparents - Carreteiro, Rui (2016)
Background: Controversy exists regarding the role played by parent-children relationships for children’s behavioral and psychosocial development. Crucial for some authors, others consider parenting styles as part of a more complex system. Less adaptive parenting styles are generally associated with childrenwhohave lower involvement at school and may contribute for psychopathology emergence. Objectives: To investigate the contribution of parenting styles for the explanation of child psychopathology. Hypothesis: Parenting styles (H1) and parents’ childhood memories regarding parenting styles (H2) do contribute significantly for the explanation of statistical variance of children’s psychopathology. Method: Participants: 110 children (67 boys, 43 girls) aged 7-11 years (M = 9.22, SD = 1.14) from schools in Portugal as well as 83 fathers and 86 mothers; Instruments: For parenting styles, the Portuguese version of EMBU memories of upbringing (for parents regarding their own parents), EMBU-P (for parents) and EMBU-C (for children) were used. To assess children’s psychopathology the Portuguese version of CBCL was used. Results: According to linear regressions, individual and family factors do contribute significantly for the explanation of all CBCL’s indexes. EMBU-C regarding mothers’ parenting styles only explains the Hyperactivity/Attention index. EMBU-P explains most of CBCL’s indexes. Mothers’ and Fathers’ EMBU Memories of Upbringing explains the overall CBCL’s indexes. Conclusions: The explanation of children’s psychopathology by parenting styles is not restricted to parents’ representations regarding their own parenting styles nor to children’s perceptions regarding parenting styles but extends to memories of parents regarding parenting styles used by theirownparents. The ability of EMBUMemoriesof Upbringing to explain children’s psychopathology seems to exceed the EMBU-P’s and EMBU-C’s capacity.